Once-daily intrapleural urokinase treatment of complicated parapneumonic effusion in pediatric patients - Bianchini, Maria Anastasia; Ceccarelli, Pier Luca; Repetto, Paolo; Durante, Viviana; Biondini, Diego; Bergamini, Barbara; Cacciari, Alfredo (The Turkish Journal of Pediatrics, 2010)
In this paper, we describe our experience in the treatment of childhood empyema using urokinase. Patients' ages ranged from 2 to 12 years. Urokinase (dosage: 3,100 IU/kg/day) was diluted in normal saline to produce 1000 IU/ml (maximum dosage 100,000 IU in 100 ml of normal saline). After 2 hours, the clamped catheters were released and connected to water-seal suction at a negative pressure of 10 cm H2O. Pleural irrigations were continued once a day until thoracostomy tube output decreased to less than 10 ml/day (urokinase treatment mean duration: 11.5 days). The complete resolution of the chest effusion was assessed on chest ultrasound scan and radiographs. None of the patients experienced any side effects due to urokinase. It would now seem reasonable to advocate small chest tube thoracostomy and intrapleural urokinase as first-line treatment of pleural empyema in children, with surgery indicated as a secondary intervention.